'An extra level of kind of torment': Views and experiences of recurrent miscarriage care during the initial phases of COVID‐19 in Ireland-A qualitative interview study - Rebecca Dennehy; Marita Hennessy; Jennifer Ui Dhubhgain; Con Lucey; Keelin O'Donoghue (Wiley, 2023)
Abstract Introduction Maternity services underwent much change during the COVID‐19 pandemic. Research on the impact on miscarriage care and experiences during this time is sparse. Within a national evaluation of recurrent miscarriage care, we qualitatively explored stakeholder views and experiences of recurrent miscarriage services in Ireland. This study describes the impact of the COVID‐19 pandemic on those experiences and perceptions of care. Methods People with professional and lived experience of recurrent miscarriage and service engagement were actively involved in this qualitative study from idea generation to analysis and reporting. We recruited women and men with two or more consecutive first‐trimester miscarriages, and people involved in the management/delivery of recurrent miscarriage services and supports. We used purposive sampling to ensure that perspectives across disciplinary or lived experience, geographical, and health service administrative areas, were included. We conducted semi‐structured interviews, virtually all due to COVID‐19 restrictions, between June 2020 and February 2021. These were audio‐recorded, and data were transcribed, and subsequently analyzed using reflexive thematic analysis. Results We interviewed 42 service providers and 13 women and 7 men with experience of recurrent miscarriage. We actively generated two central themes during data analysis. The first-'Disconnected'-describes how many women navigated miscarriage diagnosis and management and care in subsequent pregnancies alone; many felt that this resulted in increased trauma. At the same time, men struggled with not being present to support their partners and described feeling disconnected. The second theme highlighted 'The perceived dispensability of recurrent miscarriage services and supports'. Some service providers felt that service reduction and redeployment demonstrated a lack of value in the service. Virtual clinics facilitated access to services, but a preference for in‐person care was highlighted. Conclusion Our analysis provides rich insights into the significant impacts that the COVID‐19 pandemic has had on the way recurrent miscarriage care is provided and experienced, with important implications for early pregnancy, miscarriage and recurrent miscarriage care. Services have undergone significant changes and, while these may be temporary, how services should be delivered in the future requires consideration, particularly given the deficits in care and care experiences highlighted prepandemic. Patient or Public Contribution Members of the multidisciplinary RE:CURRENT Project Research Advisory Group (including four parent advocates, two of whom are co‐authors on this article) were actively involved throughout the study, including the generation of topic guides and the refining of themes.